Pengaruh Aplikasi Pupuk Organik Paitan (Tithonia diversifolia) dan Biourin Kambing Terhadap Pertumbuhan Bibit Kopi Robusta (Coffea canephora L.): Effects of Paitan (Tithonia diversifolia) Organic Fertilizer Application and Goat Biourine on the Growth of Robusta Coffee (Coffea canephora L.) Seedlings - Sulkifli Nurdin; Basri Baba; Eka Wisdawati (Jurnal Agrotan, 2025)
The growth of coffee seedlings can be supported by providing nutrients derived from Paitan Organic Fertilizer and goat Biourin. This study aims to determine the effect of paitan organic fertilizer and goat biourin on the growth of robusta coffee seedlings. This research was conducted from November 2022 to July 2023 in the Experimental Garden of the Department of Agricultural Production Technology, Pangkajene Islands State Agricultural Polytechnic. The experiment used a Randomized Block Design (RBD) with a factorial pattern, namely two factors, the first factor was the dose of paitan compost organic fertilizer (T) consisting of 4 levels, including 0 tons/ha (t0), 10 tons/ha (t1), 20 tons/ha (t2), 30 tons/ha (t3). The second factor is goat biourine (U) which consists of four levels, namely 0% (u0), 10% (u1), 20% (u2), 30% (u3), so there are 16 treatment combinations. The results showed that the treatment of paitan organic fertilizer and goat biourin gave no significant effect on the parameters of plant height and number of leaves, but gave a significantly effect on stem diameter parameters. However, the combination of the two treatments did not significantly affect all observation variables. The results of the BNT further test at the 1% level showed the treatment of paitan organic fertilizer with a dose of 30 tons/ha and goat biourin with a concentration of 30% gives a better effect than without the provision of organic fertilizer and biourin.